Mapping restricted introgression across the genomes of admixed indigenous African cattle breeds - Friedrich, J.; Bailey, R.I.; Talenti, A.; Chaudhry, U.; Ali, Q.; Obishakin, E.F.; Ezeasor, C.K.; Powell, J.; Hanotte, Olivier H.; Tijjani, Abdulfatai; Marshall, Karen; Prendergast, J.; et al. (Springer, 2023)
The genomes of indigenous African cattle are composed of components with Middle Eastern (taurine) and South Asian (indicine) origins, providing a valuable model to study hybridization and to identify genetic barriers to gene flow. In this study, we analysed indigenous African cattle breeds as models of hybrid zones, considering taurine and indicine samples as ancestors. In a genomic cline analysis of whole-genome sequence data, we considered over 8 million variants from 144 animals, which allows for fine-mapping of potential genomic incompatibilities at high resolution across the genome.We identified several thousand variants that had significantly steep clines (‘SCV’) across the whole genome, indicating restricted introgression. Some of the SCV were clustered into extended regions, with the longest on chromosome 7, spanning 725 kb and including 27 genes. We found that variants with a high phenotypic impact (e.g. indels, intra-genic and missense variants) likely represent greater genetic barriers to gene flow. Furthermore, our findings provide evidence that a large proportion of breed differentiation in African cattle could be linked to genomic incompatibilities and reproductive isolation. Functional evaluation of genes with SCV suggest that mitonuclear incompatibilities and genes associated with fitness (e.g. resistance to paratuberculosis) could account for restricted gene flow in indigenous African cattle.To our knowledge, this is the first time genomic cline analysis has been applied to identify restricted introgression in the genomes of indigenous African cattle and the results provide extended insights into mechanisms (e.g. genomic incompatibilities) contributing to hybrid differentiation. These results have important implications for our understanding of genetic incompatibilities and reproductive isolation and provide important insights into the impact of cross-breeding cattle with the aim of producing offspring that are both hardy and productive.